2016
DOI: 10.1007/s11999-016-4930-0
|View full text |Cite
|
Sign up to set email alerts
|

Is Model-based Radiostereometric Analysis Suitable for Clinical Trials of a Cementless Tapered Wedge Femoral Stem?

Abstract: Background In clinical trials of THA, model-based radiostereometric analysis (RSA) techniques may be less precise than conventional marker-based RSA for measurement of femoral stem rotation. We verified the accuracy and clinical precision of RSA based on computeraided design models of a cementless tapered wedge femoral stem. Questions We asked: (1) Is the accuracy of model-based RSA comparable to that of marker-based RSA? (2) What is the clinical precision of model-based RSA?Methods Model-based RSA was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…When comparing these trials to the current study, the clinical precisions for translations are immediately comparable, while we found better precision for rotations. Clinical precision of model‐based RSA on the glenoid component of RTSA in our study was comparable to similar studies in hips and knees…”
Section: Discussionsupporting
confidence: 89%
“…When comparing these trials to the current study, the clinical precisions for translations are immediately comparable, while we found better precision for rotations. Clinical precision of model‐based RSA on the glenoid component of RTSA in our study was comparable to similar studies in hips and knees…”
Section: Discussionsupporting
confidence: 89%
“…The secondary endpoint was the three‐dimensional migration of the femoral stem measured by model‐based radiostereometric analysis (RSA) at week 48. RSA is considered safe .…”
Section: Methodsmentioning
confidence: 99%
“…Stability and adequate distribution of bone markers were assessed by calculating mean error of rigid body fitting (upper limit ≤0.35) and condition number (upper limit ≤150) . The accuracy and precision of model‐based RSA was verified in a pretrial experiment using a phantom model . Clinical precision for each axis was determined based on double examinations of 58 trial subjects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy and precision of the applied model-based RSA technique was verified in a phantom model before the trial [15]. RSA was performed according to the RSA guidelines [16,17].…”
Section: Radiostereometric Analysismentioning
confidence: 99%